Marion zimmer bradley's sword of avalon eaudiobook - Paxson, Diana L. (Avalon, 2009)
Epic in its sweep and peopled by the remarkable women who have always inhabited Avalon, Marion Zimmer Bradley's Sword of Avalon expands the legendary saga that has enchanted millions of readers over the years and is sure to please Bradley's loyal readership and anyone who loves wonderfully told stories of history, myth, and fantasy. A boy raised in secret after traitors kill his parents will return to Avalon—and when he does, he'll be faced with a formidable task: to prove his worth as a son of the kings and priestesses of his land and lead his followers to victory, wielding the newly forged sword Excalibur.